Abnormal α‐synuclein deposits in skin nerves: intra‐ and inter‐laboratory reproducibility. (2nd August 2019) - Donadio, V.; Doppler, K.; Incensi, A.; Kuzkina, A.; Janzen, A.; Mayer, G.; Volkmann, J.; Rizzo, G.; Antelmi, E.; Plazzi, G.; Sommer, C.; Liguori, R.; et al.
Abstract : Background and purpose: Visualization of phosphorylated α‐synuclein at serine 129 (p‐syn) in skin nerves is a promising test for the in vivo diagnosis of synucleinopathies. Here the aim was to establish the intra‐ and inter‐laboratory reproducibility of measurement of intraneural p‐syn immunoreactivity in two laboratories with major expertise (Würzburg and Bologna). Methods: In total, 43 patients affected by Parkinson's disease (PD 21 patients), dementia with Lewy bodies (DLB 1), rapid eye movement sleep behaviour disorder (RBD 11), multiple system atrophy (MSA‐P 4) and small fibre neuropathy (SFN 6) were enrolled. Skin biopsy was performed at the C7 paravertebral spine region and distal skin sites (thigh or leg). The analysis was standardized in both laboratories and carried out blinded on a single skin section double stained with antibodies to p‐syn and the pan‐axonal marker protein gene product 9.5. Fifty skin sections were randomly selected for the analysis: 25 from C7 and 25 from distal sites. Differently classified sections were re‐evaluated to understand the reasons for the discrepancy. Results: The intra‐laboratory analysis showed an excellent reproducibility both in Würzburg (concordance of classification 100% of sections; K  = 1; P  < 0.001) and Bologna (96% of sections; K  = 0.92; P  < 0.001). Inter‐laboratory analysis showed reproducibility in 45 sections (90%; K  = 0.8; P  < 0.001) and a different classification in five sections, which was mainly due to fragmented skin samples or weak fluorescent signals. Conclusions: Analysis of p‐syn showed excellent inter‐ and intra‐laboratory reproducibility supporting the reliability of this technique. The few ascertained discordances were important to further improve the standardization of this technique.